Lead-free molecular ferroelectric [N, N-dimethylimidazole]3Bi2I9 with narrow bandgap. (August 2020) - Yang, Weijie; Chu, Kai-Bin; Zhang, Lixue; Ding, Xiangdong; Sun, Jun; Liu, Jefferson Zhe; Song, Jun-Ling; Zheng, Changxi; Deng, Junkai
Abstract: Lead-based organic-inorganic hybrid perovskite materials are widely applied in solar cells due to their excellent optoelectronic properties. These materials usually appear ferroelectricity with the built-in electric field, which can be used to improve the power conversion efficiency (PCE) of solar cells. However, the toxicity of lead has severely hampered their applications. Hence, it is of utmost significance to explore novel organic-inorganic hybrid perovskite materials with non-toxicity, ferroelectricity, and narrow bandgap at room temperature to enhance the PCE for broad practical applications. Herein, we reported a lead-free hybrid molecular ferroelectric material, i.e. (C5 N2 H9 )3 Bi2 I9, with zero-dimensional perovskite-like structure. (C5 N2 H9 )3 Bi2 I9 undergoes first-order ferroelectric phase transition with a Curie temperature of 327 K. Moreover, the dielectric constants of (C5 N2 H9 )3 Bi2 I9 exhibit a step-like anomaly varied between the high-temperature paraelectric phase and the low-temperature ferroelectric phase. Furthermore, (C5 N2 H9 )3 Bi2 I9 demonstrates a narrow bandgap of 2.1 eV. Hence, the as-reported novel member of the organic-inorganic hybrid family renders great promise for optoelectronic devices. Graphical abstract: Unlabelled Image Highlights: Novel organic-inorganic hybrid perovskite (C5 N2 H9 )3 Bi2 I9 was synthesized. It was designed by selecting N -methylimidazole and non-toxic metal Bi. The material has shown a paraelectric-to-ferroelectric phase transition at 327 K. This designed molecular ferroelectric also exhibit a narrow bandgap of 2.1 eV.